Deskripsi Pedagogical Content Knowledge Guru pada Bahasan tentang Pola Bilangan - Alfonsa Maria Abi; Helti Lygia Mampouw; Novisita Ratu (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2020)
The purpose of this research is to describe the teacher's Pedagogical Content Knowledge in learning of patterns. This research uses Pedagogical Content Knowledge approach with interviews with teachers and tests on class XI students in 6 (six) SMK in Salatiga. The results showed that SMK teachers had pedagogical competencies characterized by curriculum knowledge but were still lacking in knowledge about students and teaching. They have knowledge about valuation and enough knowledge about resources. Whereas in professional competence all teachers have knowledge of content and objectives but do not meet PP No. 74 of 2008 which states that professional competence is obtained through professional education. Only 1 respondent fulfilled while 5 respondents did not meet because they were not graduates of mathematics education. Thus, of the 6 respondents who were the subjects of the study, all of them did not fulfill their pedagogical competencies as teachers and only 1 respondent had met their professional competencies.